Предмет:
МатематикаАвтор:
аноним1) Сократим дроби:
а) (с^2 - 5)/(1 - √2) = (с^2 - 5) * (1 + √2)/((1 - √2) * (1 + √2)) = (c^2 - 5) * (1 + √2)/(1 - 2) = - (c^2 - 5) * (1 + √2) = -(1 + √2) * (c^2 - 5);
б) (c - √5)/(√3 - √6) = (c - √5) * (√3 + √6)/((√3 - √6) * (√3 + √6)) = (√3 + √6) * (c - √5)/(3 - 6) = -1/3 * (√3 + √6) * (c - √5);
2) Упростим выражение:
6√n/(3 * √an) = 6 * √n/(3 * √a * √n) = 6/3 * √n/(√a * √n) = 2 * 1/(√a * 1) = 2/√a;
(n - √n):(2 * √n - 2) = √n * (√n - 1)/(2 * (√n - 1)) = √n * (√n - 1)/(2 * (√n - 1)) = √n/2.
Автор:
linus798sДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть